CONTENT ANALYSIS OF THE GRADUATE THESIS AND DISSERTATIONS İN MATHEMATICS EDUCATION İN TURKEY BETWEEN 2005-2010 - Alper ÇİLTAŞ (Fırat University, 2019)
This is because the investigation of educational studies and their proper organization will help the other researchers who want to conduct related studies. In this study, master theses and dissertations in mathematics education published between 2005 and 2010 in Turkey are examined. For this purpose, 150 theses and dissertations retrieved from the thesis centre in the Turkish Council of Higher Education (YOK) were examined. The publication classification form was used to examine the relevant theses. As a result of the study, it was found that the use of quantitative method was high, most frequent areas studied in mathematics education included teaching, majority of the samples involved in the studies were primary education (6-8) and the sample size ranged from 31 to 100 in